PENGEMBANGAN MEDIA ‘’ASIH ‘’ UNTUK MENINGKATKAN KEMAMPUAN PRONOUNCIATION DAN SPEAKING SISWA SLOW LEARNERS DI SDN BALEREJO 02 - Sulasih; Mochamad Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aims of This research to optimize the application of Asih media as a learning medium to improve pronunciation skills for slow learner students in SDN BALEREJO 02 MADIUN. Students with difficulties in learning English, especially in pronunciation, often face challenges related to sound recognition and proper intonation. Therefore, the use of Asih media which can convert text into sound is considered an effective solution in helping students to listen and imitate correct pronunciation. This research applies experimental methods with quantitative and qualitative approaches, which involve measuring students' pronunciation abilities before and after using Asih media. It is hoped that the results of this research will provide empirical evidence about the effectiveness of using Asih media in improving the pronunciation skills of slow learner students, as well as contributing to the development of more inclusive and technology-based English language learning methods.